Promotion of Cultural Heritages Through A Virtual Museum Platform: Case Study Hagia Sophia - Cem Kırlangıçoğlu; Mehmet Fatih Döker (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The DigitalWorld has become the most significant platform for spreading the written andvisual documents about cultural and historical heritages in accordance with therecent developments on web based technologies. All kind of digital platformssuch as notebooks, personal computers, tablets and mobile phones are theprimary tools to transfer local values to global scale. Nevertheless, it is notpossible to say that these technological opportunities are not used efficientlyto promote museums keeping the inheritance and memory of societies.Fortunately, 3D game technologies and virtual reality applications have beenstarted to use in this area. The traditional promotion methods are beingreplaced by these new and innovative solutions including ‘virtual museum’ term.People are capable to use this platform to see and interactively walk throughthe virtually reconstructed museums in a 3D digital environment. Creatingaccessible web based virtual museum platforms will attract tourists, studentsand researchers from all ages. The aim of this study is to create a virtualmuseum platform including all kind of written and visual materials. HagiaSophia has been selected as the case study area of this study and digitallyreconstructed to use in the project.